Refrigerant Alternatives for High Speed Train A/C Systems: Energy Savings and Environmental Emissions Evaluation under Variable Ambient Conditions. (November 2016) - Mastrullo, R.; Mauro, A.W.; Vellucci, C.
Abstract: The environmental concerns due to global warming are pushing A/C industries to new eco-friendly refrigerants in several fields. In this paper a model to simulate the dynamic evolution of the temperature inside an air-conditioned high-speed train compartment is presented. The dynamic modeling of both the reversible heat pump unit and the thermal loads of the cabin are presented, including the possibility of adapting the frequency of the compressor and the return air fraction for maintaining the internal comfort conditions. Under different dynamic load conditions (in terms of ambient temperature, solar radiation, train speed, number of passengers) the energy consumptions and the TEWI related to the use of new refrigerants, (like R1234yf and R1234ze), are calculated being the R134a a baseline for comparison.